A Fe3O4 / HNT composite catalytic material, its preparation method and application
Patent Information
- Application Number
- CN202611361163.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]针对现有技术存在的纳米Fe3O4易团聚、非均相类芬顿催化剂活性位点少、pH适用窗口窄、载体未改性时活性组分负载不均,循环使用性能差的技术缺陷,本发明旨在提供一种Fe3O4/HNT复合催化材料及其制备方法和应用
通过采用煅烧-硫酸酸刻蚀联合预处理埃洛石纳米管载体,调控载体表面孔结构与表面官能团,再通过溶剂热原位生长方式负载Fe3O4,促使Fe3O4纳米颗粒高度均匀分散,颗粒粒径稳定控制在50-150nm,极大缓解Fe3O4纳米颗粒团聚问题,暴露更多催化活性位点。SEM、TEM表征证实,预处理后的HNT可以抑制Fe3O4颗粒长大团聚;对比例纯Fe3O4颗粒粒径处于200-500nm,团聚现象严重。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of post-fire pollution control and organic wastewater treatment technology, specifically relating to a supported Fe3O4 / HNT composite catalytic material and its preparation method, and particularly to the application of this composite catalytic material in the emergency treatment of polycyclic aromatic hydrocarbon fire-fighting wastewater after a fire. Background Technology
[0002] During a fire, the incomplete combustion of various building, decorative, and polymer materials generates large amounts of toxic polycyclic aromatic hydrocarbons (PAHs). These substances can enter water bodies and soil environments along with fire-fighting flushing wastewater. PAHs possess a stable structure with fused aromatic rings, making them difficult to biodegrade. They also exhibit strong bioaccumulation, mutagenicity, and carcinogenicity, seriously threatening the post-disaster ecological environment and human health.
[0003] Existing technologies for treating wastewater containing polycyclic aromatic hydrocarbons (PAHs) mainly include physical adsorption, biodegradation, and advanced oxidation processes. Physical adsorption can only achieve phase transfer of pollutants and cannot completely mineralize and decompose them; biodegradation has a long treatment cycle and poor applicability in post-disaster emergency scenarios. Fenton advanced oxidation technology can generate highly oxidizing reactive oxygen species, mineralizing organic pollutants into CO2 and H2O, with high treatment efficiency. Traditional homogeneous Fenton systems must operate under strongly acidic conditions at pH 2-3, and generate a large amount of iron sludge solid waste after the reaction, resulting in high subsequent treatment costs and limiting practical application in the field.
[0004] Heterogeneous Fenton technology can overcome the aforementioned defects of homogeneous Fenton. Magnetite Fe3O4, possessing both an inverse spinel crystal structure and superparamagnetic properties, is a highly promising catalytic material in the heterogeneous Fenton field. However, nano-Fe3O4 has high surface energy and is prone to particle agglomeration due to magnetic dipole interaction in aqueous solutions, resulting in a decrease in specific surface area, loss of catalytic active sites, and a significant reduction in catalytic performance.
[0005] Existing technologies utilize Fe3O4 loading onto supports to mitigate agglomeration issues, but conventional loading processes have significant drawbacks: Fe3O4 nanoparticles are unevenly distributed on the support surface, particle size is difficult to precisely control, and the overall improvement in catalyst activity is limited. In emergency treatment scenarios for fire-fighting wastewater, catalytic materials are required to adapt to complex water qualities, a wide pH range, rapid reaction rates, and quick recovery and reuse; existing catalysts struggle to meet these practical engineering needs.
[0006] Therefore, developing a Fe3O4-based composite Fenton catalyst with good dispersibility, wide pH applicability, easy magnetic recovery, and excellent cycle stability is of great practical significance for the emergency treatment of polycyclic aromatic hydrocarbon wastewater after fires. Summary of the Invention
[0007] To address the technical shortcomings of existing technologies, such as the easy aggregation of nano-Fe3O4, the limited number of active sites in heterogeneous Fenton-like catalysts, the narrow pH application window, the uneven loading of active components when the support is not modified, and the poor recyclability, this invention aims to provide a Fe3O4 / HNT composite catalytic material, its preparation method, and its application.
[0008] According to the present invention, halloysite nanotube carriers are first subjected to calcination-acidification composite pretreatment, and then a solvothermal in-situ loading process is adopted to achieve uniform and controllable loading of Fe3O4 nanoparticles, thereby obtaining a highly active composite catalytic material. This material can efficiently degrade polycyclic aromatic hydrocarbons under a wide pH range, and the magnetic separation and recovery are simple, with good cycle stability, making it suitable for emergency treatment of fire-fighting wastewater containing polycyclic aromatic hydrocarbons after a fire.
[0009] Specifically, according to a first aspect of the present invention, a method for preparing a Fe3O4 / HNT composite catalytic material is provided, comprising the following steps: Step 1: Pretreatment of Halloysite Nanotube Carrier Natural halloysite nanotubes (HNTs) were calcined in air at 500-700℃ for 2-5 hours to obtain the calcined product; the calcined product was then added to... Acid etching was carried out by stirring in sulfuric acid solution at 50-80℃ for 4-12 hours with a solid-liquid ratio of 0.5%-2.0%. After acid treatment, the solid was collected by centrifugation and washed with deionized water until the pH of the filtrate was neutral. The washed solid was dried at 100-120℃ for 8-16 hours to obtain pretreated halloysite nanotubes T-HNT.
[0010] Further preferred, the calcination temperature is 600℃, and the calcination time is 3 hours; the sulfuric acid solution concentration... Solid-liquid ratio 1.0%; acid treatment temperature 60℃, acid treatment time 8h; drying temperature 110℃, drying time 12h.
[0011] Step 2: Synthesis of Fe3O4 / HNT composite catalyst by solvothermal method The iron salt and the T-HNT obtained in step one were dispersed in a polyol solvent and stirred for 1-3 hours. Citrate was added, and the mixture was sonicated and stirred for another 0.5-1 hour to obtain a homogeneous dispersion. Acetate was added to the dispersion and stirred for 3-10 minutes to obtain a viscous mixture. The mixture was transferred to a high-pressure reactor and subjected to a solvothermal reaction at 180-220°C for 14-22 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The solid product was collected by centrifugation and washed alternately with deionized water and ethanol until the washing solution was neutral. The product was dried at 50-70°C for 4-10 hours to obtain the Fe3O4 / HNT composite catalyst.
[0012] More preferably, the iron salt is ferric chloride hexahydrate. The polyol solvent used is ethylene glycol; the stirring time for the first step is 2 hours; the citrate is sodium citrate dihydrate; the citrate concentration... More preferably Ammonium acetate was selected as the acetate; the solvothermal reaction temperature was 200℃ and the reaction time was 20h; the drying temperature was 60℃ and the drying time was 6h.
[0013] Furthermore, the loading of Fe3O4 on T-HNT is 10%-50% of the mass of T-HNT; more preferably, the loading is 20wt%. If the loading is too low, there will be insufficient catalytic active sites; if the loading is too high, the Fe3O4 nanoparticles will re-aggregate, reducing catalytic performance and exacerbating the ineffective consumption of hydrogen peroxide.
[0014] According to a second aspect of the present invention, a Fe3O4 / HNT composite catalytic material is provided, which is prepared by any of the above preparation methods; wherein Fe3O4 nanoparticles are uniformly loaded on the surface of pretreated halloysite nanotubes in the composite catalytic material, and the Fe3O4 particle size is 50-150 nm; the surface of the catalytic material is rich in hydroxyl groups and oxygen vacancies, and the proportion of OH / oxygen vacancies to total oxygen species reaches 70.42%; the material has superparamagnetic properties.
[0015] According to a third aspect of the present invention, the above-mentioned Fe3O4 / HNT composite catalyst is provided for the treatment of wastewater containing polycyclic aromatic hydrocarbons, particularly for the Fenton-like catalytic degradation of polycyclic aromatic hydrocarbon pollutants in fire-fighting wastewater after a fire.
[0016] Furthermore, the polycyclic aromatic hydrocarbon is naphthalene; the degradation process is as follows: the composite catalytic material is added to the wastewater containing polycyclic aromatic hydrocarbons, hydrogen peroxide is added, and a Fenton-like catalytic degradation reaction is carried out at room temperature; the pH of the reaction system is controlled at 3-9.
[0017] Furthermore, the catalytic degradation process parameters include: catalyst dosage. Initial concentration of H2O2 .
[0018] The composite catalytic material relies on the pretreatment of the HNT support to achieve the pre-enrichment of naphthalene molecules, and the hydroxyl groups on the support surface capture the enriched molecules through hydrogen bonding. Electron-containing naphthalene molecules reduce mass transfer resistance; Fe on the material surface 2+ Active sites activate H2O2 to generate hydroxyl radicals Fe 3+ Further reaction with H2O2 to achieve Fe 2+ Regeneration, while simultaneously generating superoxide anion free radicals. Hydroxyl radicals are the dominant active species for degrading naphthalene, while superoxide anion radicals play a synergistic role in degradation. The active radicals directly attack naphthalene molecules pre-enriched at the catalyst interface, mineralizing naphthalene through ring opening into CO2, H2O, and small-molecule organic intermediates. Iron leaching experiments show that the highest iron concentration leached during the reaction is only [missing information]. lower than the EU The emission limits are based on the fact that the vast majority of the degradation process occurs at the catalyst solid-liquid interface, with homogeneous Fenton contributing only 4.6%.
[0019] According to the present invention, at least the following beneficial effects are achieved: By employing a combined calcination-sulfuric acid etching pretreatment of halloysite nanotubes (HNTs) to regulate the surface pore structure and functional groups, and then loading Fe3O4 via solvothermal in-situ growth, highly uniform dispersion of Fe3O4 nanoparticles was achieved, with particle sizes stably controlled within the 50-150 nm range. This significantly alleviated the Fe3O4 nanoparticle aggregation problem and exposed more catalytic active sites. SEM and TEM characterization confirmed that the pretreated HNTs could inhibit the growth and aggregation of Fe3O4 particles; in contrast, the pure Fe3O4 particles in the comparative sample had a particle size of 200-500 nm and exhibited severe aggregation.
[0020] Because the composite catalytic material of this invention has a large number of hydroxyl groups and oxygen vacancies on its surface, the hydroxyl groups can enrich polycyclic aromatic hydrocarbon substrates such as naphthalene in the solution through hydrogen bonding; the oxygen vacancies can accelerate electron transfer, promote the iron cycle of the system, continuously activate H2O2 to generate hydroxyl radicals, and enhance the degradation capacity of pollutants. Although the BET specific surface area of the composite material is reduced compared with pure HNT after loading, the adsorption capacity for naphthalene is actually improved by interfacial chemisorption, achieving substrate pre-enrichment, reducing free radical quenching loss, and improving oxidant utilization efficiency.
[0021] This invention's catalyst breaks through the narrow pH limitation of traditional Fenton catalysts, maintaining high catalytic activity across a wide pH range of 3-9. Under optimal conditions, the naphthalene degradation efficiency exceeds 98% within 5 minutes; even in a weakly alkaline environment at pH=9, the naphthalene removal rate still reaches 77.38% after 15 minutes, making it suitable for the actual working conditions of fire-fighting wastewater with large pH fluctuations after fires. Traditional homogeneous Fenton catalysts can only achieve efficient treatment at pH 2-3, requiring the addition of large amounts of strong acid for fire-fighting wastewater with a neutral or weakly alkaline pH after disasters. This invention eliminates the need for significant pH adjustment, reducing the amount of reagent required.
[0022] The catalytic material exhibits superparamagnetism, enabling rapid solid-liquid separation and recovery using an external magnetic field. After five cycles, the naphthalene degradation efficiency remains above 85%, demonstrating excellent reusability and reducing processing costs. XRD comparison before and after the reaction shows that the catalyst's crystal structure was not significantly damaged, with only a slight decrease in peak intensity, mainly due to the adsorption of organic degradation intermediates covering the active sites, indicating stable bulk material structure.
[0023] Under simulated fire conditions with complex wastewater matrix (containing inorganic salts and humic acid interference substances), this material still maintains a naphthalene removal rate of over 95%, demonstrating strong anti-interference capabilities and suitability for emergency response at fire sites. For Cl... - NO3 - Commonly coexisting anions exhibit good tolerance; HCO3 - CO3 2- HPO4 2- While altering the system's pH level may slightly inhibit degradation efficiency, it still maintains a considerable treatment effect. The overall preparation process is simple, the raw materials are readily available, and the production cost is low, making it suitable for large-scale production and promotion.
[0024] The degradation mechanism was elucidated through free radical quenching experiments. It is the dominant active species for degrading naphthalene. It plays a secondary synergistic role; it is clear that the system is mainly based on heterogeneous interface catalysis, and the contribution of homogeneous Fenton from iron dissolution is very low, which confirms that the material itself is the core of the catalytic effect, with little loss of active components and low risk of secondary pollution. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to the embodiments. Those skilled in the art will understand that the description is exemplary and the present invention is not limited to the specific embodiments.
[0026] Example 1 This embodiment provides a method for preparing a Fe3O4 / HNT composite catalytic material, comprising the following steps: Step 1: Halloysite Nanotube Pretreatment Natural halloysite nanotubes (HNT) were calcined in air at 600℃ for 3 hours; the calcined product was then added to... A sulfuric acid solution with a solid-liquid ratio of 1.0% was stirred at 60°C for 8 hours for acid etching. The solid was collected by centrifugation, washed with deionized water until the filtrate was neutral, and dried at 110°C for 12 hours to obtain T-HNT. The calcination process dehydrated the HNT, and the sulfuric acid etching dissolved the aluminum component, resulting in a modified halloysite nanotube carrier rich in defect sites and hydroxyl sites.
[0027] Step 2: Solvent-thermal synthesis of composite catalytic materials Pick 1.500 g T-HNT was dispersed in 90 mL ethylene glycol and stirred for 2 h; 0.285 g sodium citrate dihydrate was added, and the mixture was sonicated and stirred for another 0.5 h; 1.311 g ammonium acetate was added and stirred for 5 min; the mixture was transferred to a 150 mL high-pressure reactor and reacted at 200 °C for 20 h using a solvothermal method; the mixture was cooled to room temperature, centrifuged, and washed alternately with deionized water and anhydrous ethanol until neutral; the mixture was dried at 60 °C for 6 h to obtain a Fe3O4 / HNT composite catalyst with a loading of 20 wt%.
[0028] The material obtained in this embodiment was characterized by a series of SEM and TEM studies. The Fe3O4 particles, ranging from 50 to 150 nm, were uniformly dispersed on the outer wall of the THNT tubular structure without obvious agglomeration. XPS tests showed that -OH / oxygen vacancies accounted for 70.42% of the total oxygen species. The material exhibited superparamagnetism. XRD detected the (111)(220)(311)(400)(511)(440) diffraction peaks of the Fe3O4 crystal planes.
[0029] Example 2 The process was largely the same as in Example 1, except that the solvothermal reaction time in step two was adjusted to 16 hours, while all other parameters remained unchanged, to prepare the Fe3O4 / HNT composite catalytic material. The shortened solvothermal time resulted in a slight decrease in the crystallinity of Fe3O4 and a slightly lower catalytic activity compared to the sample in Example 1.
[0030] Example 3 Degradation performance test Take the composite catalyst material prepared in Example 1 and add it to 50 mL. Naphthalene aqueous solution, catalyst dosage Adjust the pH to 3.0 with HCl; add H2O2 to adjust the initial concentration. The naphthalene-like degradation was carried out by stirring at room temperature. Samples were taken periodically, filtered through a 0.22 μm filter membrane, and the residual naphthalene concentration was detected by high-performance liquid chromatography at 220 nm.
[0031] Test results: Under pH=3 conditions, the naphthalene degradation efficiency was >98% after 5 minutes, and the apparent rate constant k was [missing value]. obs =0.684min -1 At pH 9, the naphthalene removal rate was 77.38% after 15 min; the degradation efficiency was greater than 85% after 5 cycles. SEM and TEM showed that the Fe3O4 particles were 50-150 nm in size and uniformly dispersed; XPS analysis showed that OH / oxygen vacancies accounted for 70.42% of the total oxygen species.
[0032] Free radical quenching verification experiments were conducted: tert-butanol (TBA) was added as a hydroxyl radical quencher, and benzoquinone (BQ) was added as a superoxide anion radical quencher. After adding TBA, the naphthalene degradation efficiency decreased by 52.16% within 5 minutes; after adding BQ, the naphthalene degradation efficiency decreased by 22.73% within 5 minutes. This demonstrates that hydroxyl radicals are the dominant active species in this system, while superoxide anion radicals play a synergistic auxiliary role in degradation.
[0033] Iron leaching test: Under optimal reaction conditions, the system dissolves the highest amount of iron ions. lower than the EU Emission limits; homogeneous contribution accounts for only 4.6% of the total degradation effect, with the vast majority of degradation occurring at the catalyst solid-liquid interface.
[0034] TOC mineralization test: The TOC removal rate of the system reached 65.4% after 60 minutes of reaction, indicating that naphthalene was not only removed by adsorption, but most of it was mineralized into inorganic small molecules.
[0035] Comparative Example 1: Pure Fe3O4 nanoparticles Without adding the T-HNT carrier, the remaining operations were performed as in step two of Example 1 to prepare pure Fe3O4. Under the same degradation conditions as in Example 3, the naphthalene degradation efficiency was only 58.2% after 60 minutes. obs =0.014 min -1 SEM images showed severe particle aggregation, with particle sizes ranging from 200 to 500 nm. The lack of a support for confinement led to the large-scale aggregation of nanoparticles, encapsulating active sites and significantly deteriorating catalytic performance.
[0036] Comparative Example 2: Untreated Natural HNT Carrier Raw natural HNT was used directly instead of T-HNT, without calcination-acid etching pretreatment; the rest of the process was completely consistent with Example 1. In Example 3, under the same degradation conditions, the catalytic activity was significantly lower than that of Example 1; SEM showed uneven distribution of Fe3O4 particles and obvious agglomeration. Raw HNT lacked calcination-acid etching modification, resulting in insufficient surface active sites and poor anchoring ability for Fe3O4.
[0037] Comparative Example 3: H2O2 Blank System Without adding a catalyst, and with all other conditions remaining the same as in Example 3, only H2O2 was added. The naphthalene degradation efficiency was less than 7%, proving that hydrogen peroxide alone is almost unable to degrade naphthalene, and that a catalyst is needed to activate hydrogen peroxide to generate active free radicals.
[0038] Application Example 1: Simulation of Post-Fire Wastewater Treatment Preparation of simulated fire-fighting wastewater: naphthalene , , humic acid Degradation tests were conducted using the reaction conditions of Example 3. The naphthalene degradation efficiency was ≥95% in 5 minutes, demonstrating that the composite catalytic material of the present invention still has excellent treatment effect in complex actual wastewater matrices and is suitable for emergency treatment after fire disasters.
[0039] Further experiments were conducted to investigate the interference of coexisting anions: 10 mM Cl was added to the system. - NO3 - The naphthalene removal rate remained above 95% after 10 minutes; the addition of 10mM HCO3... - CO3 2- HPO4 2- It will change the pH of the system, and the degradation efficiency will drop to 71%-75%, but it still has the ability to degrade; under the condition of humic acid, the degradation performance of the system is not inhibited, and even slightly improved. The material has strong resistance to complex water quality interference.
[0040] In summary, the present invention has been described in detail through specific embodiments. However, those skilled in the art will understand that various modifications and changes can be made, and as long as they do not depart from the spirit and purpose of the present invention, all such modifications and changes should fall within the protection scope of the present invention, which is defined by the appended claims.
Claims
1. A method for preparing a Fe3O4 / HNT composite catalytic material, characterized in that, Includes the following steps: Step 1: Pretreatment of Halloysite Nanotubes Natural halloysite nanotubes (HNT) were calcined in air at 500-700°C for 2-5 hours to obtain the calcined product. Add the calcined product Sulfuric acid solution, solid-liquid ratio 0.5%-2.0%, stirred at 50-80℃ for 4-12h for acid treatment; collect solid residue by centrifugation, wash with deionized water until the pH of the filtrate is neutral; dry the solid at 100-120℃ for 8-16h to obtain pretreated halloysite nanotubes T-HNT; Step 2: Synthesis of Fe3O4 / HNT composite catalyst Iron salt and the T-HNT were dispersed in a polyol solvent and stirred for 1-3 hours. Citrate was added, and the mixture was sonicated and stirred for another 0.5-1 hour to obtain a homogeneous solution. Acetate was added and stirred for 3-10 minutes to obtain a mixed viscous liquid. The mixed viscous liquid was placed in a high-pressure reactor and subjected to a solvothermal reaction at 180-220°C for 14-22 hours. The mixture was cooled to room temperature, and the solid was collected by centrifugation. The solid was washed alternately with deionized water and ethanol until neutral. The solid was dried at 50-70°C for 4-10 hours to obtain the Fe3O4 / HNT composite catalyst.
2. The preparation method according to claim 1, characterized in that, In step one: the calcination temperature is 600℃, and the calcination time is 3 hours; the concentration of the sulfuric acid solution is... The solid-liquid ratio was 1.0%; the acid treatment temperature was 60℃ and the acid treatment time was 8h; the drying temperature was 110℃ and the drying time was 12h.
3. The preparation method according to claim 1 or 2, characterized in that, Step 2: The iron salt is ferric chloride hexahydrate; the polyol solvent is ethylene glycol; the citrate is sodium citrate dihydrate; the acetate is ammonium acetate; the solvothermal temperature is 200℃, and the solvothermal time is 20h; the drying temperature is 60℃, and the drying time is 6h.
4. The preparation method according to claim 1 or 3, characterized in that, The Fe3O4 loading mass fraction relative to T-HNT is 10%-50%, preferably 20%; the citrate concentration is... Preferred .
5. The preparation method according to claim 4, characterized in that, The Fe3O4 loading mass fraction relative to T-HNT was 20%; the citrate concentration was... .
6. A Fe3O4 / HNT composite catalytic material, characterized in that, The material is prepared by any one of the preparation methods described in claims 1-5; the Fe3O4 nanoparticles are uniformly loaded on the surface of pretreated halloysite nanotubes, and the Fe3O4 particle size is 50-150 nm; the surface of the catalytic material is rich in hydroxyl groups and oxygen vacancies, and has superparamagnetism.
7. The application of the Fe3O4 / HNT composite catalytic material according to claim 6, characterized in that, Used for Fenton-like catalytic degradation treatment of wastewater containing polycyclic aromatic hydrocarbons.
8. The application according to claim 7, characterized in that, The polycyclic aromatic hydrocarbon is naphthalene; the wastewater is fire-fighting wastewater after a fire.
9. The application according to claim 7, characterized in that, The composite catalytic material was added to wastewater containing polycyclic aromatic hydrocarbons, and hydrogen peroxide was added to carry out a Fenton-like degradation reaction at room temperature; the pH of the reaction system was 3-9.
10. The application according to claim 9, characterized in that, Catalyst dosage Initial concentration of H2O2 .